Acceptability of telehealth-delivered rehabilitation: Experiences and perspectives of people with traumatic brain injury and their carers. (February 2022) - Rietdijk, Rachael; Power, Emma; Attard, Michelle; Togher, Leanne
Introduction: Communication skills training for people with traumatic brain injury (TBI) and their carers is recommended best practice. Delivery via telehealth could improve access to this training. This paper focuses on the acceptability of telehealth delivery of communication skills training. Methods: A mixed-methods investigation of acceptability of telehealth to people with TBI and their carers was incorporated into a clinical trial. Thirty-six people with TBI (23 metropolitan and 13 regional) and their carers were recruited. Metropolitan participants were randomly allocated to telehealth or in-person intervention at a 1:3 ratio. Regional participants were allocated to telehealth. Telehealth and in-person participants were compared on retention, time to complete the programme, home practice completion and therapeutic alliance ratings. Participants completed semi-structured interviews regarding their views on telehealth, which were analysed using thematic analysis. Results: There were no significant differences between telehealth and in-person participants in retention rate, time to complete the programme, degree of home practice completion or therapeutic alliance ratings. Three themes were identified: 'telehealth delivery opens a window for access to rehabilitation in the context of my daily life', 'in-person delivery offers rehabilitation based on natural human interaction' and 'weighing telehealth against in-person delivery'. Discussion: Participants found telehealth delivery acceptable, as indicated by the similarity between groups in the quantitative process measures, and as reported in interviews. Some reported a preference for in-person delivery if there had been a choice of delivery mode. Participants described characteristics of the two delivery modes which were relevant to their attitudes towards telehealth.